Pergeseran Tradisi Manganan Perahu - Lukman Lukman Al Khafidz (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2019)
Tradition is a part of people's lives, there is always accompanying the journey of human life, various traditions in society are the product of human's own creation, always guarded and passed down from generation to generation. That is what happened to the tradition of manganan paerahu in the village of Palang in Tuban district, the tradition of manganan perahu which is a legacy from ancestors is always routinely carried out every year. However, along with the passage of time and the pattern of community life, the tradition of manganan perahu also experienced changes from the procedures for implementation and various equipment. The tradition of a boat mackerel that was initially syncretistic and even tended to be thick with nuances to Hindu eventually experienced a shift towards Islamic manganan perahu traditions. Strengthening the values ​​to Islam that occurred in the community of Palang was allegedly the main factor causing the change in the implementation of the tradition of manganan perahu from culture to Hinduan to Islam.